EFEKTIVITAS MEDIA SATE BILANGAN DAN KUBUS WARNA TERHADAP PENINGKATAN PEMAHAMAN KONSEP MATEMATIS SISWA SEKOLAH DASAR - furqon al hadiq, muhamad; Nurjanah, Erni; Novia Vini Syafitri, Yoesrina; Gilang Mas Ramadhan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Conceptual understanding is a fundamental component of mathematics learning in primary education, and concrete manipulatives are often recommended to support students’ transition from real objects to symbolic representation. This study examines the effectiveness of two concrete learning media (Sate Bilangan and Colored Cubes) in facilitating students’ conceptual understanding of whole numbers and basic arithmetic operations. A quantitative approach was employed using a quasi-experimental design that involved a control group and two experimental groups. The test instruments were validated prior to use, and data were analyzed through prerequisite testing, analysis of variance, and post hoc procedures to identify differences between groups. The use of both concrete media led to improved conceptual understanding compared to conventional instruction. Sate Bilangan helped students recognize number structure through directed manipulative activities, whereas Colored Cubes strengthened understanding of place value and regrouping through spatial representation. Analysis of conceptual indicators showed that both media supported gains in areas related to representation and students’ ability to restate mathematical ideas. No meaningful difference in effectiveness was observed between the two media. Concrete manipulatives provide meaningful support for primary mathematics learning by guiding students through gradual conceptual development and reducing cognitive load when working with mathematical symbols. Future research may extend the scope of content, explore combinations of concrete and digital media, or investigate long-term retention and the role of mathematics anxiety in diverse classroom contexts.